The Strategic Exploitation of Conspiracy Theories by Populist Leaders - Eirikur Bergmann (Genealogy)
Populist leaders have strategically exploited conspiracy theories as powerful political tools to shape national identities, delegitimise opponents, and consolidate their authority. This paper examines the historical genealogy of conspiratorial populism, tracing its evolution across distinct political and economic crises from the 1970s to the present. Using a threefold analytical framework—(1) constructing external threats, (2) demonising domestic elites, and (3) positioning populists as the defenders of the “pure people”—the study demonstrates how conspiracy theories have been central to the rise and endurance of nativist populism. By analysing key historical waves—ranging from the economic turmoil of the 1970s, the collapse of communism, the post-9/11 security environment, the 2008 financial crisis, and the 2015 refugee crisis, to the COVID-19 pandemic and ongoing geopolitical conflicts—this paper highlights how conspiratorial narratives have been repeatedly adapted to shifting socio-political contexts.